Isolation and Partial Purification of Cell wall Lipopolysaccharides of Pseudomonas Aeruginosa and Using It as Vaccine - Taghreed A. Mohammad; Sawsan Abdul Hussain Mahdi (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
This study ,the samples were   collected from "118 patients " suffering from burn wound contaminated with Pseudomonas aeruginosa and 100 health individuals (male and female ) as a control group ,the samples were wound swap and blood sample  .       Chromatography technique was employed to extract and purify cell wall containing lipopolysaccharide by using P. aeruginosa  isolate ATCC 15692,the purification done by addition of ammonuium sulfate, sodium dodecyl sulfat (SDS) anddialysis, gel filtration chromatography by using sepharose-4B.       Immunogenicity of  LPS component was determined by mice injection under the skin  ,then Ab concentration against LPS component formed and determined by ELISA .       These findings indicated ability of LPS to make immune system stimulated to release specific Ab towards  P. aeruginosa  isolate ATCC 15692  , therefore, this result may be a promising procedure to produce vaccine against P. aeruginosa  isolate ATCC 15692.